Canadian Association of Gastroenterology Clinical Practice Guidelines: The Use of Tumour Necrosis Factor-Alpha Antagonist Therapy in Crohn’s Disease - Daniel C Sadowski; Charles N Bernstein; Alain Bitton; Ken Croitoru; Richard N Fedorak; Anne Griffiths; the CAG Crohn’s Consensus Group (Canadian Journal of Gastroenterology)
BACKGROUND: Guidelines regarding the use of infliximab in Crohn’s disease were previously published by the Canadian Association of Gastroenterology in 2004. However, recent clinical findings and drug developments warrant a review and update of these guidelines.